Night owl eaudiobook - Jenkins, Emily (Upside-Down Magic, 2021)
The Upside-Down Magic kids are back in another topsy-turvy adventure in the next installment of this New York Times bestsellingseries! It's Big Night in Dunwiddle . . . and that means the whole school has a sleepover like no other. For one night every year, magicstudents run through the halls, hunting for the objects that will win them a super special prize.Nory is super excited for the scavenger hunt. Not only because she likes winning, but also because if her team wins, she thinksthere's a chance her best friend Elliott won't move away to attend super snobby Sage Academy.Sebastian is a little less excited once the hunt is on. Yes, he has magical powers that help his team — like being able to seeinvisible things or anything that makes a sound. The problem is that the really loud sounds are hurting him . . . and nobody seemsto care.The kids in Upside-Down Magic know their five F's (Flares, Flyers, Fuzzies, Flickers, and Fluxers) — but to win this night, a sixth Fis the most important . . . Friendship.